IMAGOLOGY: ON USING ETHNICITY TO MAKE SENSE OF THE WORLD - Leerssen, Joep (Porównania, 2018)
This article outlines the theory and method of imagology, the discursive study of ethnotypes (stereotypical attributions of national character). Imagology has a respectable history and academic presence, but adjustments are needed in the light of recent developments. These include: [a] the replacement of the national- modular categorization of literary traditions by a polysystemic approach; [b] the decline of print fiction as a the premier narrative medium, and the rise of film, TV, and other media; [c] the realization that ethnotypes are often encountered in occluded form (deployed ironically or as “meta-images”; or in a «banal» or latent background presence, as dormant frames); [d] new, «intersectional» notions of identity formation; [e] the demise of Eurocentrism and the rise of postnationalism. While these emerging challenges call for an adjustment of imagological analysis, the present climate of identity politics also demonstrates an ongoing, indeed urgent need to address what remains the core business of imagology: deconstructing the discourse of national and ethnic essentialism.